The design of an information system for managing teaching staff salaries - Maastri, Adi; S, Ahmad (Journal of Computer Science Application and Engineering (JOSAPEN), 2025)
Effective management of teaching staff salaries is crucial for maintaining operational efficiency and ensuring employee satisfaction within educational institutions. Traditional manual systems often suffer from inefficiencies, data inconsistencies, and security risks, highlighting the need for a dedicated solution tailored to salary management. This study addresses this gap by designing a comprehensive information system that automates and streamlines salary-related processes. Utilizing the waterfall development methodology, the system was structured through sequential phases of analysis, design, coding, testing, and implementation. The proposed system incorporates key features such as user authentication, hierarchical access control, and automated periodic salary updates. It accommodates multiple user roles, including teachers, financial operators, and administrators, ensuring secure and role-specific access to salary data. Use case and activity diagrams were developed to illustrate the system’s functionality, including login validation and the submission of salary update forms. By bridging the gap between theoretical frameworks and practical implementation, this study contributes a robust, user-friendly solution that enhances transparency and reduces administrative workload.